Application of a fenton process after a biological nitrification treatment : a successful case for leachate treatment - Traid, Hernán Darío (2022)
Fil: Traid, Hernán Darío. Consejo Nacional de Investigaciones Científicas y Técnicas. Instituto de Materiales de Misiones; Argentina.